Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5530/pj.2019.11.108
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Anti-Urolithiasis Potential of Traditional Siddha Formulations Amukkara Chooranam and Karisalai Karpam Chooranam by Struvite Crystal Growth Inhibition Assay

Abstract: Background: Urolithiasis is a medical condition characterized by formation of stone which comprises of calcium oxalate, magnesium ammonium phosphate and uric acid. Reoccurrence becomes the primary hindering factor in providing relief for urolithiasis; hence there is a need of alternate therapeutic strategy that may effectively combat and halt the formation and nucleation of the crystals. Objective: The main aim of the present investigation is to explore the anti-urolithiasis potential of the two versatile sidd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The technical methods for standardization of herbal drugs include chromatographic and spectroscopic analysis, chemical parameters, microbiological parameters, pharmacognostic evaluation, physicochemical parameters etc. 11 .…”
Section: Standardization Of Siddha Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The technical methods for standardization of herbal drugs include chromatographic and spectroscopic analysis, chemical parameters, microbiological parameters, pharmacognostic evaluation, physicochemical parameters etc. 11 .…”
Section: Standardization Of Siddha Medicinementioning
confidence: 99%
“…A literature search revealed that three reports on the scientific validation of Amukkara Chooranum deal with the physicochemical and HPTLC assessment of the Chooranum 8,9,10 . The authors (D. Sivaraman et al,) demonstrated Amukkara Chooranum for strong antilithogenic effects due to therapeutic phytochemicals interacting with ions that produce urolithiasis crystals and prevent their formation and aggregation 11 . Amukkara Chooranum Tablet was one of the Siddha Sasthric Medicines in Fixed Regimen (SSM-FiRe) given to the COVID -19 patients with asymptomatic and mild symptomatic category as an oral dose and the regimen had safe, no modification in biochemical parameters 12 .…”
mentioning
confidence: 99%
“…Siddha system of medicine signifies great history of treating infective pathogens since centuries. [7][8] Herbal medicine comprises of bioactive therapeutics with viable pharmacological properties. Siddha formulations known for managing infectious disorders without major side/adverse effects because of its unique and reliable combination of herbal ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Most significant pharmacophores of the existing drugs are derived from the herbal origin. Versatile functional group and side chain moieties synergies the affinity of receptor binding and thereby offers expected pharmacological activity [6][7][8][9] . On folklore basis metabolites from numerous herbs are known for managing diseases and disorders around the globe…”
Section: Introductionmentioning
confidence: 99%